2002
DOI: 10.1046/j.1445-5994.2002.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and experimental uses of umbilical cord blood

Abstract: Umbilical cord blood (UCB) has been used successfully as an alternative source of haemopoietic stem cells (HSC) in allogeneic stem-cell transplantation for the treatment of acquired and genetic diseases. Advantages of using UCB include: (i) no risk to the donor, (ii) no donor attrition, (iii) minimal risk of viral transmission and (iv) immediate availability. Early results have highlighted differences in engraftment rates and toxicity between UCB and other sources of HSC. These differences relate to the low ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
1
13
0
1
Order By: Relevance
“…The procedures takes about 5 min and poses no risk to mother or baby. Cord blood has emerged as an alternative to bone marrow because of its greater availability, weak immunogenicity, and lower risk of mediating viral transmission (52). Umbilical cord blood banking provides enough number of CD34 + cells needed for a clinical benefit in man.…”
Section: Figmentioning
confidence: 99%
“…The procedures takes about 5 min and poses no risk to mother or baby. Cord blood has emerged as an alternative to bone marrow because of its greater availability, weak immunogenicity, and lower risk of mediating viral transmission (52). Umbilical cord blood banking provides enough number of CD34 + cells needed for a clinical benefit in man.…”
Section: Figmentioning
confidence: 99%
“…6 -9 Cord blood has emerged as an alternative to bone marrow because of its greater availability, weak immunogenicity, and lower risk of mediating viral transmission. 10 We have reported significant behavioral benefit after intravenous infusion of human umbilical cord blood cells (HUCBC) in the rat middle cerebral artery occlusion (MCAO) model of stroke. 8,11 Moreover, we demonstrated that intravenous infused HUCBC was comparable to, if not better than, intrastriatally transplanted HUCBC in mediating behavioral recovery after MCAO.…”
mentioning
confidence: 99%
“…More recently, peripheral blood (after treatment of the donor with cytokines to mobilize stem cells) has been found to be a better source of stem cells to restore hematopoiesis (85). Umbilical cord blood (UCB) can also be used and has several advantages over bone marrow as a source of HSCs, especially in pediatric patients (86). In principle, the HSCs are the only cells required to restore the ablated hematopoietic system.…”
Section: Stem Cell Therapiesmentioning
confidence: 99%